2011
DOI: 10.9746/jcmsi.4.29
|View full text |Cite
|
Sign up to set email alerts
|

On Internal Stabilizing Mechanism of Passive Dynamic Walking

Abstract: : In this paper, the relationship between the internal stabilizing mechanism of passive dynamic walking and linear optimal control is investigated. In contrast to existing results, it is shown that the stabilizing mechanism can be characterized as a special type of optimal control. After verifying the feasibility of such a formulation numerically, it is proved that the internal stabilizing feedback coincides with a cheap optimal control law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These results suggest that the adaptive behavior, which is caused by the change in the internal parameters of the legged robot, appears actually in the experimental environment. In addition, referring the numerical simulations in conventional studies, transitions among the simulative conditions caused by the adaptive behavior are reversible [5,6]. Thus, even in the experimental conditions, it can be expected that the transitions of the adaptive behavior are also reversible.…”
Section: Verification Of Adaptive Behaviormentioning
confidence: 95%
See 1 more Smart Citation
“…These results suggest that the adaptive behavior, which is caused by the change in the internal parameters of the legged robot, appears actually in the experimental environment. In addition, referring the numerical simulations in conventional studies, transitions among the simulative conditions caused by the adaptive behavior are reversible [5,6]. Thus, even in the experimental conditions, it can be expected that the transitions of the adaptive behavior are also reversible.…”
Section: Verification Of Adaptive Behaviormentioning
confidence: 95%
“…It is well known that passive dynamic walking shows characteristic behaviors owing to changes in the internal or external environment [1][2][3][4][5][6][7]. In addition, passive dynamic walking shows "adaptive behaviors" in which a passive dynamic walking robot adjusts its gait to keep walking in a continuously changing walking environment during walking.…”
Section: Introductionmentioning
confidence: 99%
“…By using this analytical Poincaré map, Sugimoto and Osuka [23] showed that the implicit feedback structure contributes to its stability. Recently, by further developing the concept proposed by Sugimoto et al, Hirata [28] clearly showed that the implicit feedback structure in PDW can be characterized as cheap optimal control. Moreover, Owaki et al [29] constructed an actual passive dynamic bipedal running device and performed running experiments; the device achieved a running performance of as many as 36 steps in the real world.…”
Section: Previous Related Studiesmentioning
confidence: 98%
“…While the lower energy-consumption makes these passive walkers sensitive to mechanical parameter variation and external disturbances, any tiny modification of parameters could lead to an obvious change on the gait [9]- [10]. [11] and [12]- [13] do the research on the influence of each parameter to single-periodic stable walking gait of the straight compass gait model. Passive-dynamic walkers can exhibit period doubling and apparently chaotic gaits.…”
Section: Introductionmentioning
confidence: 99%